The Frequency of Clinic Visits Was Not Associated with Medication Adherence or Outcome in Children with Inflammatory Bowel Diseases - Cheryl Kluthe; Jenkin Tsui; Donald Spady; Matthew Carroll; Eytan Wine; Hien Quoc Huynh (Canadian Journal of Gastroenterology and Hepatology)
Background. Medication nonadherence is a challenge in pediatric patients with inflammatory bowel diseases (IBD). Poor adherence can result in disease flare-ups, disease complicationstherapy escalation, and the need for corticosteroids. The aim was to determine if clinic visit frequency was associated with treatment adherence. Methods. A retrospective chart review of patients attending the Edmonton Pediatric IBD Clinic (EPIC) at the Stollery Children’s Hospital from January 2012 to December 2013 was completed. Correlations were made between frequency of clinic visit, percentage of prescriptions filled, percentage of requisitioned blood work completed, rural or urban residence, and steroid-free remission status of patients for the 6 months after the chart review. Results. 127 patients were reviewed with 82 patients diagnosed with Crohn’s disease (CD) and 46 with ulcerative colitis (UC) which included one IBD-Unclassified. Mean age at diagnosis is 9.17 years and median duration of follow-up is 3.2 years. Almost all patients on infliximab infusions received them “within window.” Immunomodulator median adherence rate was 88%. 5-ASA adherence was 82%. A median of 67% of patients had blood work completed as requested. Clinic visit frequency was not associated with adherence to blood work or to medications. Duration of disease was the only independent factor found to be associated with a reduction in blood work and immunomodulator adherence (“OR 0.86 and 95% CI: 0.74–0.99” and “OR 0.82 and 95% CI: 0.71–0.97”) per year, respectively. Patients who remained corticosteroid-free in the 6 months after the 2 years’ adherence review had an overall median medication adherence rate of 86% compared to only 53% for those who relapsed and required corticosteroids (p=0.01). Conclusion. Clinic visit frequency was not associated with patient adherence to medications or blood work. However, disease duration was found to be associated with medication adherence. Adherent patients were more likely to remain in steroid-free remission.